Thrust optimization of linear oscillatory actuator using permeance analysis method - Misron, Norhisam; Abdul Shukor, Fairul Azhar; Hizam, Hashim; Nirei, Masami; Wakiwaka, Hiroyuki; Jelani, Abdul Razak (2008)
This paper is described on optimization the thrust of linear oscillatory actuator (LOA). The objective of this optimization is to obtain the high thrust of LOA with restricted weight of LOA due to requirement of application. In this paper, the thrust optimization is done using permeance analysis method (PAM). The FEM and measurement result were use to verified the PAM result. As a result, the LOA has been designed with having optimum parameter and high thrust.